Morphological Variation of Primary Reproductive Structures in Males of Five Families of Neotropical Bats - Beguelini, Mateus R. [UNESP]; Puga, Cíntia C. I. [UNESP]; Martins, Fabiane F. [UNESP]; Betoli, André H. S. [UNESP]; Taboga, Sebastião R. [UNESP]; Morielle-Versute, Eliana [UNESP] (Wiley, 2013)
Bats present unique features among mammals with respect to reproduction, and although neotropical bats do not have a hibernation period, many of their reproductive characteristics vary seasonally and interspecifically. Thus, this work aimed to examine the reproductive structures of 18 species belonging to five families of Brazilian bats. The gross anatomy of the testes varied little; however, the epididymis of Emballonuridae and Vespertilionidae showed exceptional structures with a large elongation of the caudal region. We observed a wide variation in the positioning of the testes: Phyllostomidae and Noctilionidae presented external testes; Emballonuridae and Molossidae presented migratory testes that may be in intra-abdominal or external positions; and Vespertilionidae displayed scrotal testes. In the histological evaluation, we observed a different pattern in vespertilionid species, with testicular regression and sperm retention/storage in the cauda epididymis in the five species analyzed. Similar testicular regression was observed in Molossops temminckii; however, sperm retention/storage was not observed in this species. These data suggest that although the species analyzed are tropical species that do not present a prolonged period of torpor (hibernation), they still maintain a period of seminiferous tubule regression and sperm storage very similar to that observed in hibernating bats. © 2012 Wiley Periodicals, Inc.
Keywords: Chiroptera; Epididymis; Quiescence; Testes; Vespertilionidae; anatomical variation; animal experiment; bat; controlled study; Emballonuridae; epididymis; hibernation; histology; male; male genital system; Molossops temminckii; morphology; Neotropics; Noctilionidae; nonhuman; Phyllostomidae; priority journal; scrotum; sperm; sperm preservation; testis; Animals; Brazil; Epithelium; Male; Organ Size; Species Specificity; Spermatozoa; Testis; Mammalia; Molossidae